Net Zero Strategies in State Owned Energy Firms - Pudjono, Alpha Nur Setyawan; Wibisono, Dermawan; Sulaeman, Dwi Rian; Asbah, Zuhwan; Bangun, Madju Yuni Ros; Purwadi, Agus; Halim, Didi Kurniadi; Putri, Aghnia Nadhira Aliya; Maulanda, Fadrian Dwiki; Sonia, Veren; Shihran, Reza Setiadi; Hibban, Laksamana Naufal; Anugia, Zakie; Priyanto, Rohmat (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study investigated renewable energy strategies in Malaysia, Denmark, and Japan to derive actionable insights for Indonesia’s energy transition. The objective was to explore effective approaches for achieving net-zero emissions in state-owned energy enterprises within developing countries. A comparative analysis methodology was employed, incorporating benchmarking interviews with policymakers, industry experts, and regulators from the three countries, as well as the review of official energy strategy documents. Malaysia emphasized diversifying its energy mix through supportive policies and advancements in solar, hydro, and biomass technologies. Denmark achieved remarkable success through a liberalized energy market and robust regulatory support, particularly for wind power. Japan, shaped by its post-Fukushima context, focused on energy independence via investments in solar, wind, and geothermal technologies. The findings revealed that Indonesia could benefit from adopting a diversified energy portfolio, establishing stable policy frameworks, increasing investments in research and development, modernizing its power grid, and engaging local communities. This study concluded that aligning Indonesia’s energy policies with technological capabilities and regulatory environments is essential to achieving a sustainable energy transition and meeting net-zero targets.